Totally laparoscopic and totally robotic surgery in patients with left‐sided colonic diverticulitis. Issue 1 (7th January 2020) - Bilgin, Ismail Ahmet; Bas, Mustafa; Benlice, Cigdem; Esen, Eren; Ozben, Volkan; Aytac, Erman; Baca, Bilgi; Hamzaoglu, Ismail; Karahasanoglu, Tayfun
Abstract: Background: Introduction of the da Vinci Xi system has facilitated the use of robotics in colorectal surgery. Nevertheless, data on the outcomes of robotic surgery for the treatment of colonic diverticulitis have remained scarce. Methods: Patient demographics, clinical characteristics, and perioperative outcomes of the patients undergoing totally robotic with the da Vinci Xi system or laparoscopic surgery for left‐sided colonic diverticulitis (LCD) were compared. Results: Laparoscopic and robotic groups included 22 and 20 patients, respectively. There were no significant differences between the two groups in terms of patient demographics, clinical characteristics, operative time, and postoperative complications. There were three conversions in the laparoscopy group and no conversion in the robotic group ( P = 0.23). Conversion to open surgery was associated with postoperative morbidity ( P = 0.02). Conclusion: Robotic surgery is an applicable alternative for the treatment of LCD. Robotic approach may potentially lower the risk of operative morbidity by reducing the requirement of conversion.